Pengaruh Return On Assets, Debt To Equity Ratio, Proporsi Dewan Komisaris Independen Dan Ukuran Perusahaan Terhadap Tax Avoidance - Melia Wida Rahmayani; Wulan Riyadi; Yogi Ginanjar (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2021)
Tax Avoidance has its own uniqueness because one side of tax avoidance is permissible, but on the other hand tax avoidance is undesirable because it will harm state revenues. (Judi and Setiyono, 2012). Ten years ago Indonesia had an illegal flow of money of Rp2,254 trillion, this was due to the practice of tax evasion and tax avoidance that occurred in the palm oil sector which cost the country Rp.45.9 trillion (Republika article, 2015). This study aims to find empirical evidence about the effect of retrun on assets, debt to equity ratio, the proportion of independent commissioners and company size on tax avoidance. The sample in this study were 255 company data by determining the sample using a purposive sampling technique and obtained a sample of 51 companies. Data analysis method used in this research is multiple linear regression. The results of this study indicate that retrun on assets and firm size affect tax avoidance. Debt to equity ratio and the proportion of independent board of commissioners have no effect on tax avoidance.